Evaluation of intratumoral heterogeneity by using diffusion kurtosis imaging and stretched exponential diffusion-weighted imaging in an orthotopic hepatocellular carcinoma xenograft model - Guo, Ran; Yang, Shuo-Hui; Lu, Fang; Han, Zhi-Hong; Yan, Xu; Fu, Cai-Xia; Zhao, Meng-Long; Lin, Jiang (Quantitative Imaging in Medicine and Surgery; Vol 9, No 9 (September 25, 2019): Quantitative Imaging in Medicine and Surgery, 2019)
Background: To investigate the value of diffusion kurtosis imaging (DKI) and diffusion-weighted imaging (DWI) with a stretched exponential model (SEM) in the evaluation of tumor heterogeneity in an orthotopic hepatocellular carcinoma (HCC) xenograft model. Methods: Thirty orthotopic HCC xenograft nude mice models were established and randomly divided into two groups, the sorafenib induction group (n=15) and control group (n=15). Every mouse in each group underwent MRI with DKI and SEM on a 1.5T MR scanner at 7, 14, and 21 days after sorafenib intervention. DKI and SEM parameters including mean kurtosis (MK), mean diffusivity (MD), α, and distributed diffusion coefficient (DDC) were measured, calculated, and compared between the two groups and among different time points. Sequential correlations between histopathological results including necrotic fraction (NF), micro-vessel density (MVD), Ki-67 index, standard deviation (SD), and kurtosis from hematoxylin-eosin staining, and DKI and SEM parameters were analyzed. Results: MK, MD, and DDC of HCC in the sorafenib induction group were significantly higher than those in the control group at each time point (P